Developing Engaged and Entrepreneurial Universities Theories, Concepts and Empirical Findings - Kliewe, Thorsten; Kesting, Tobias; Plewa, Carolin; Baaken, Thomas (Springer Nature Singapore : Imprint: Springer, 2019)
XI, 260 p. 15 illus., 4 illus. in color.